What drives growth in water utility firms after equitization? Evidence from Vietnam - To, Uyen Diep (International Journal of Management and Sustainability, 2025)
This paper analyzes Vietnam's water utilities following equitization to determine whether firm growth is related to certain relevant variables widely discussed in the existing literature. These include ownership structure, size, years since equitization, leverage, population density, return on total assets, and macroeconomic variables. The study examined a sample of 62 listed water utility firms from 2019 to 2023 using STATA, and the hypothesis was tested through logistic regression. The research outcomes indicate that state ownership (OWN) positively and significantly influences revenue growth (RGR) across OLS, REM, and GLS models (p < 0.01), but does not significantly impact profit growth (PGR). Financial leverage (LEV) has a statistically significant positive effect on both RGR and PGR, suggesting that debt plays a constructive role in firm growth within this sector. Firm age (AGE) demonstrates a consistent and significant negative relationship with both RGR and PGR (p < 0.01), highlighting the risk of stagnation following equitization. ROA is strongly and positively associated with firm growth in all models (p < 0.01), emphasizing the importance of asset efficiency. Among macroeconomic variables, the real interest rate (RIR) exhibits a surprising positive effect on RGR and PGR in specific models, while GDP growth positively and significantly influences both growth indicators. Although inflation (INF) is negative, it is statistically insignificant. The results support policymakers and managers in promoting the sustainable growth of water utility firms after equitization.